Proapoptotic Function of the MET Tyrosine Kinase Receptor through Caspase Cleavage - Tulasne, David (American Society for Microbiology, 2004)
The MET tyrosine kinase, the receptor of hepatocyte growth factor-scatter factor (HGF/SF), is known to be essential for normal development and cell survival. We report that stress stimuli induce the caspase-mediated cleavage of MET in physiological cellular targets, such as epithelial cells, embryonic hepatocytes, and cortical neurons. Cleavage occurs at aspartic residue 1000 within the SVD site of the juxtamembrane region, independently of the crucial docking tyrosine residues Y1001 or Y1347 and Y1354. This cleavage generates an intracellular 40-kDa MET fragment containing the kinase domain. The p40 MET fragment itself causes apoptosis of MDCK epithelial cells and embryonic cortical neurons, whereas its kinase-dead version is impaired in proapoptotic activity. Finally, HGF/SF treatment does not favor MET cleavage and apoptosis, confirming the known survival role of ligand-activated MET. Our results show that stress stimuli convert the MET survival receptor into a proapoptotic factor.